2012
DOI: 10.5935/1678-9741.20120009
|View full text |Cite
|
Sign up to set email alerts
|

Características clínico-demográficas de pacientes submetidos a cirurgia de revascularização do miocárdio e sua relação com a mortalidade

Abstract: Características clínico-demográficas de pacientes submetidos à cirurgia de revascularização do miocárdio e sua relação com a mortalidadeDemographic and clinical characteristics of patients undergoing coronary artery bypass graft surgery and their relation to mortality Abstract Objective: To describe the demographic and clinical characteristics of patients undergoing coronary artery bypass graft surgery (CABG) and to test their relation to mortality. Methods: This study was a retrospective medical record review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 27 publications
3
18
0
7
Order By: Relevance
“…As well, in another study in Santa Catarina/Brazil, the authors found the same relationship [15]. In our study, we found that age ≥ 65 years was not a predictor of mortality, similar to other reported by Ng et al [16] in a retrospective study with 1594 patients undergoing CABG alone, where no significant difference in hospital mortality between patients aged ≥ 70 years (5.4%) compared to those with less than 70 years (3.8%).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…As well, in another study in Santa Catarina/Brazil, the authors found the same relationship [15]. In our study, we found that age ≥ 65 years was not a predictor of mortality, similar to other reported by Ng et al [16] in a retrospective study with 1594 patients undergoing CABG alone, where no significant difference in hospital mortality between patients aged ≥ 70 years (5.4%) compared to those with less than 70 years (3.8%).…”
Section: Discussionsupporting
confidence: 67%
“…We found studies that described their groups of elderly with age ≥ 65 years-old [12], ≥ 70 yearsold [13][14][15][16][17], ≥ 75 years-old [6,21], ≥ 80 years-old [22] and ≥ 85 years-old [23]. Therefore we will suggest that more studies to be made in order to can to conclude in which age the risks factors of this surgery appear enlarged, whether preoperative, intraoperative or postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…O principal grupo de complicações pós-operatórias foi o de hemorragia ou baixo débito, que ocorreu em mais da metade dos casos, seguido pelos grupos de problemas cardiológicos não isquêmicos, isquêmicos, respiratórios, insuficiência renal aguda, afecções infecciosas e neurológicas, todos com percentuais acima de 10% (12) . A infecção superficial é definida como sendo aquela que ocorre até 30 dias após a realização da cirurgia, envolve somente pele ou tela subcutânea e, no mínimo, um dos seguintes aspectos, drenagem purulenta com ou sem confirmação laboratorial; organismos isolados de cultura colhida de forma asséptica da secreção ou tecido superficial; sinais flogísticos ou incisão superficial aberta pelo cirurgião (13) .…”
Section: Methodsunclassified
“…As alterações pulmonares surgem a partir de inúmeros fatores, principalmente em virtude do uso de circulação extracorpórea, que ocasiona discretas alterações metabólicas e eletrolíticas no paciente, deixando-o mais suscetível às infecções (1) . Observou-se maior prevalência de disfunção renal, com evolução para IRA em torno de 7% a 30% (5,(13)(14) .…”
Section: Methodsunclassified
“…The literature reveals higher rates of morbidity and mortality in women than in men undergoing CABG (22) .…”
mentioning
confidence: 99%